Determination of the learning needs of doctors working in the Mountain Plan in Cienfuegos province. - Manuel Fernández Urquiza (Medisur)
Introduction: It is of great importance for the country´s educational strategy the constant studying of the staff already formed either technically or professionally . The actions within the Post graduate subsystem have been growing in organisation and maturity. The learning are determined and priorised taking into account the improving principles of the determination of the health personnel needs, the population needs and their level of satisfaction. Objectives: To carry out the diagnosis of the professional´s learning needs who are working at hospitals and consultations offices at the Turquino Plan in Cienfuegos province. Method: It is a qualitative research . The universe is formed by the staff working at the 2 hospitals and the 18 consultation offices at the Turquino Plan in Cienfuegos. The methods used are: Observation, Interviews to experts, Surveys and Group Dynamics. The techniques were applied taking into consideration David Leyva´s deductive model and Peter Park Investigation in Action. Results: learning needs were identified derived from professional competence . The Infrastructure problems that limit such competence was also defined